Bactericidal and hemolytic activities of synthetic peptides derived from granulysin - Siano, Alvaro (2010)
Fil: Siano, Alvaro. Universidad Nacional del Litoral. Facultad de Bioquímica y Ciencias Biológicas. Departamento de Química Orgánica; Santa Fe, Argentina.